Assessing the Organisational Climate for Secondary School Teachers Based on Gender and Locality of School - ASADULLAH, MD; YEASMIN, MINARA (JOURNAL OF INDIAN EDUCATION, 2025)
Assessing variety of aspects that contribute to the overall work environment and culture of the school is necessary when evaluating the organisational climate for secondary school teachers. Main objectives are to assess the quality of organisational climate and compare for secondary school teachers with respect to various components based on gender and locality of school. In this descriptive study, with the application of mixed method research design a total of 403 teachers have been considered as sample from the population of secondary school teachers in West Bengal, randomly. Mean, SD, t-test and SPSS-20.0 version for quantitative analysis and convergent parallel method has been used to analyse the qualitative data. There is no significant difference with respect to gender (t-value=0.663, P=0.508>0.05) and locality (t-value=0.726, P=0.468>0.05) to their organisational climate. Male teachers have better knowledge of leadership, and organisational structure and design; and female teachers are found to be better in interpersonal relations and member quality; and also rural school teachers are better at member quality, and organisational structure, and design while urban school teachers are better at knowledge about interpersonal relations and leadership among different components of organisational climate